Legal Responsibilities of Taxpayers Intentionally Not Reporting SPT Correctly - Rogantino Sampetua Pasaribu (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2024)
The source of revenue in Indonesia was divided into two: domestic revenue and foreign revenue. In this regard, tax was one of the sources of domestic revenue. The tax was also one of the largest revenue sources for Indonesia. The tax collected by the state on its citizen included income tax, value added tax, sales tax on luxury goods, revenue stamp, and certain land and building tax. Likewise one of the cases that would be analyzed by the recent research was how was the legal sanction given to the taxpayers who intentionally not reporting tax return properly. Thus, it could reduce state income and hamper public welfare. Such problem was really unfortunate and unexpected since this problem could lead state losses in terms of infrastructure development or national or international economy. The research design used in arranging this recent research was normative research. Article 39th of Tax Law has regulated that whoever deliberately failed to submit his tax return, or submit the tax return, but the information and content was false and incomplete, which might harm state revenue, would be subject to criminal sanction. The fulfillment in tax payment was really required, but when this thing was not fulfilled by those taxpayers, they would be subject to legal sanction, since they did not fulfill what they were supposed to do. The sanction would be in form of administrative sanction and also criminal sanction. Those legal sanctions were more prioritized for the taxpayers who deliberately failed to submit their tax return properly, which might subject them to legal sanction.